Postprocessing (wet-etching) of hollow-core optical fibers for enhanced transmission - Tan, Natasha Si Ning (Nanyang Technological University, 2024)
Unlike the fibers we use today, hollow core fibers can transmit light in the ultraviolet region. However, they cannot be used efficiently due to existing resonance wavelengths where signals are lost. This project achieved a broader transmission band in the ultraviolet to infrared region by improving a wet-etch post process. A lower range of resonance wavelengths was achieved when the fiber capillaries were sealed, flow rate modified and etched from both sides. The principle of selectively warming the fiber, adding hydrochloric acid, and fiber annealing were discussed. This study contributes to the development of optical fibers and their applications in the ultraviolet region. Although the transition to hollow core fibers will be gradual, it possesses a high potential to be widely adopted. Hence, it will be beneficial for continuous further research in this area.